A tannin-derived zirconium-containing porous hybrid for efficient Meerwein–Ponndorf–Verley reduction under mild conditions. Issue 1 (4th December 2019) - Leng, Yan; Shi, Langchen; Du, Shengyu; Jiang, Jiusheng; Jiang, Pingping
Abstract : Tannin-derived zirconium-containing porous hybrid exhibits excellent activity and stability for Meerwein–Ponndorf–Verley reduction under mild conditions. Abstract : Both the use of renewable natural sources to prepare catalytic materials and the Meerwein–Ponndorf–Verley (MPV) reduction for carbonyl compounds are very attractive topics in catalysis. In this study, tannins were simply assembled with zirconium in water for the scalable preparation of a heterogeneous zirconium–tannin hybrid catalyst (Zr-tannin). Various characterizations demonstrated the formation of robust porous inorganic–organic frameworks and strong Lewis acid–base sites in Zr-tannin. The cooperative effect of these acid–base sites and the abundant porosity endowed Zr-tannin with a remarkable catalytic performance for the MPV reduction of a broad range of carbonyl compounds to alcohols with 2-propanol under mild conditions. Moreover, Zr-tannin exhibited good recyclability for at least five reaction cycles. This novel strategy using tannins as the raw materials to construct heterogeneous catalytic materials may have a huge potential for green chemical synthesis due to low cost, nontoxicity, and sustainability.